EXAMINING THE HUMAN RESOURCE ARCHITECTURE RELATIONSHIP WITH EMPLOYEE PRODUCTIVITY OF CHEMICAL INDUSTRIES - Khan, Khalida; Khan, Muhammad Ali; Thebo, Jalil Ahmed; Ahmed, Tanveer; Rahoo, Liaquat Ali (The journal of contemporary issues in business and government, 2021)
The purpose of the study was to examine the human resource architecture with employee’s productivity of chemical industries of Nooriabad. The purpose of the organization is big or small formation that with specific intent has created to achieve a specific goal. Enterprise architecture is a set of principles, rules, standards and guidelines that led the design of all components of the organization and how the relationships between these components. The method of the study was the descriptive survey and correlational study. The population of the study was employees of the chemical industries of Nooriabad. The sample size of the study was 200 from the whole population of employees. A simple random sample technique was used for data collection. Questionnaire was used as an instrument for data collection and data were analyzed in SPSS Software. The result shows that there is a significant relationship between human resources architecture and its dimensions with labor productivity with the help of Person correlation test, univariate and multivariate regression Strategic Human Resource Management (SHRM) has the greatest impact on labor productivity and then value-based human resources management has the greatest impact on labor productivity of Chemical industries.